2005
DOI: 10.1024/0301-1526.34.2.108
|View full text |Cite
|
Sign up to set email alerts
|

Determination of amputation level in ischaemic limbs using tcPO2 measurement

Abstract: Our study showed that tcPO2 is a reliable indicator of local ischemia. The integration of this parameter with other personal clinical criteria may be a valuable help to the surgeon in decision making.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(24 citation statements)
references
References 11 publications
0
22
0
2
Order By: Relevance
“…By the year 2000, Misuri et al 36 validated that the accuracy threshold of TcPO2 is 20 mm Hg again in 30 lower limbs of 20 patients. In 2005, Poredos et al 37 measured TcPO2 on the dorsum of the foot and 10 cm below the knee on 56 patients before surgery to identify the lower threshold value of TcPO2. Their results were that when TcPO2 value ranged from 25 mm Hg to 36 mm Hg, the reamputation rate was 15% due to the nonhealing wound and the minimal TcPO2 value to anticipate the healing of residual limb was 15 mm Hg.…”
Section: Amputation Level Determinationmentioning
confidence: 99%
“…By the year 2000, Misuri et al 36 validated that the accuracy threshold of TcPO2 is 20 mm Hg again in 30 lower limbs of 20 patients. In 2005, Poredos et al 37 measured TcPO2 on the dorsum of the foot and 10 cm below the knee on 56 patients before surgery to identify the lower threshold value of TcPO2. Their results were that when TcPO2 value ranged from 25 mm Hg to 36 mm Hg, the reamputation rate was 15% due to the nonhealing wound and the minimal TcPO2 value to anticipate the healing of residual limb was 15 mm Hg.…”
Section: Amputation Level Determinationmentioning
confidence: 99%
“…72 In vascular disease management, peripheral blood flow measurement has a long history of use in determining the level of lower limb amputation. 73,74 In the field of PU management, blood flow monitoring has largely been limited to research applications. [75][76][77][78] However, Coggrave and Rose showed that transcutaneous blood oxygen measurement can readily be incorporated into clinical seating evaluations and can provide valuable insights for improving PU prevention practice.…”
Section: Blood Flow Measurement: Tissue Oxygen and Blood Flowmentioning
confidence: 99%
“…No contexto clínico as variáveis microcirculatórias são utilizadas como ferramentas de prognóstico para avaliar a isquémia grave dos membros [8] , a evolução da ferida cutânea [9] e, até para determinar o nível de amputação. [10] A Fluxometria por Laser Doppler (FLD), a Gasimetria Transcutânea e a Evaporimetria são tecnologias amplamente utilizadas que permitem uma avaliação sensível, contínua, não-invasiva e em tempo real de variáveis relacionadas com a circulação. [11][12][13][14] Estas técnicas são normalmente associadas a testes de provocação que podem estimular a reatividade vascular e, portanto, investigar a resposta fisiológica evocada sob controlo.…”
Section: Introductionunclassified
“…[7] Clinically, microcirculatory variables are also used as prognostic tools to assess severe limb ischemia, [8] wound outcome [9] and also to eventually determine the amputation level. [10] Laser Doppler Flowmetry (LDF), Transcutaneous Gasimetry and Evaporimetry are extensively used technologies that enable sensitive, continuous, non-invasive and real-time assessment of circulation related variables. [11][12][13][14] Frequently, these techniques are coupled with provocation tests to stimulate vascular reactivity and therefore to investigate the physiological response evoked under control.…”
Section: Introductionmentioning
confidence: 99%